UPAYA REUNIFIKASI TAIWAN DITINJAU DARI PERKEMBANGAN KONFLIK SELAT TAIWAN PERIODE 1981-1991 - Prayogi, I Gede Candra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2014), 2014)
ABSTRACT   The civil war that occurred in China between the Communists and the Nationalists won by the Communists controlled mainland China as well. Nationalists were defeated, out of China and Taiwan as well as occupying three islands off the coast that Jinmen, Mazu, and Dazhen. Communist China tried to invade Taiwan and the third island away from the other coast to complement China. Conflict occurs when crossing the Communists attempted to occupy Taiwan, while Taiwan wants to be independent. Since going on the Taiwan Strait conflict, China and Taiwan are closed to each other each "opponent" they are. This of course results in China and Taiwan as it were a separate region. China does not want Taiwan to be its own country (independent) so that invade Taiwan to be able to invade Taiwan back. However, be aware that through the invasion of China, Taiwan is not going back to China. Plus, the encouragement of international conflict between the two countries so that this can be resolved by peaceful means. To that end, China's approach to Taiwan through "initiatives Beijing" as an attempt reunification of Taiwan. At that time, the conflict in the Taiwan Strait was a quiet period. Peace of the Taiwan Strait period circa 1962-1994. Taiwan reunification efforts can be evaluated from the activity of the Taiwan Strait, especially in economic relations. Keywords : Taiwan Strait conflict, foreign policy, China-Taiwan reunification